A study at 30th street. (March 2019) - Liberman, Kenneth
Abstract: Traffic's order exceeds what traffic signs and laws are capable of regulating, and local collaborative work by motorists resolves many problems. A videotaped study of traffic flow at a busy intersection controlled by four-way stop signs revealed that when strict adherence to rules and signs impedes traffic flow, regulations may be ignored. Some ethnomethods that drivers used to maintain efficient order are identified and described, and the contrast between ethnomethodological analysis and formal analyses of order is illustrated. After a review of sociological thinking about social solidarity, the notions of the "production" of order and "structure" in social affairs are given new specifications. Highlights: Shows that traffic's order exceeds what traffic signs and laws are capable of regulating. Shows how local collaborative work by motorists resolves many problems of coordination. Identifies ethnomethods motorists use at four-way stop in the US. Argues that when strict adherence to rules and signs impedes traffic flow, regulations may be ignored. Respecifies the notions of the "production" of order and "structure" in social affairs.